Endangered : biodiversity on the brink - Tobin, Mitch (Golden, Colo. : Fulcrum Pub., 2010)
Using a species list from the American Southwest, author Mitch Tobin examines the Endangered Species Act on what it has accomplished, where it has failed, and how it could be better.--[book jacket]
Saving -- A fierce green fire -- Scopes versus squirrels -- Take me to the river -- A movement -- Political science -- Cub -- Ghost of the desert -- Blame game -- Friends of the frogs -- Warming up -- Kangaroo court -- No bats, no tequila? -- The rancher's revenge -- El tigre -- Living with el lobo -- Battling the blob -- Damn the dam? -- Effluence -- Get the lead out -- Epilogue : triage -- 12-step plan for recovery.
Includes bibliographical references (p. [421]-457) and index.
Keywords: Biodiversity conservation; Biodiversity conservation -- Southwest, New; Endangered species; Endangered species -- Southwest, New; Wildlife recovery; Wildlife recovery -- Southwest, New; Biodiversity; Biodiversity -- Southwest, New